2007
DOI: 10.1074/jbc.m704250200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CLEC12B, an Inhibitory Receptor on Myeloid Cells

Abstract: Activation of immune cells has to be tightly controlled to prevent detrimental hyperactivation. In this regulatory process molecules of the C-type lectin-like family play a central role. Here we describe a new member of this family, CLEC12B. The extracellular domain of CLEC12B shows considerable homology to the activating natural killer cell receptor NKG2D, but unlike NKG2D, CLEC12B contains an immunoreceptor tyrosine-based inhibition motif in its intracellular domain. Despite the homology, CLEC12B does not ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…This nonfunctional isoform appears to be preferentially expressed in certain tissues, including the lung, mammary gland and ovary. Although the receptor was not detected on any peripheral blood leukocyte, its expression was induced upon the differentiation of monocytes into macrophages (Hoffmann et al , 2007). CLEC12B possesses an ITIM sequence (VxYxxL) within its cytoplasmic tail, which can recruit the inhibitory phosphatases, SHP-1 and SHP-2, and, using a model system, was shown to be able to inhibit certain cellular functions.…”
Section: Clec12bmentioning
confidence: 99%
“…This nonfunctional isoform appears to be preferentially expressed in certain tissues, including the lung, mammary gland and ovary. Although the receptor was not detected on any peripheral blood leukocyte, its expression was induced upon the differentiation of monocytes into macrophages (Hoffmann et al , 2007). CLEC12B possesses an ITIM sequence (VxYxxL) within its cytoplasmic tail, which can recruit the inhibitory phosphatases, SHP-1 and SHP-2, and, using a model system, was shown to be able to inhibit certain cellular functions.…”
Section: Clec12bmentioning
confidence: 99%
“…26 Mouse and human NK cells were isolated and cultured also as previously described. 27,28 Cell lines used in this study were HeLa and 721.221 cells transduced with sCD107a or CLEC12B 29 as a control.…”
Section: Cellsmentioning
confidence: 99%
“…CLEC12B was identified in human macrophages [20], and correspondingly mRNA is expressed in monocytic cell lines and primary myeloid cells [21]. Sequences are available for CLEC12b in mouse (protein homology to human sequence: 72%) and predicted in dog (81%) and cow (80%).…”
Section: Clec12bmentioning
confidence: 99%
“…Interestingly, a putative ortholog of human CLEC12B has been identified in platypus [34], which shares 26% identity with human CLEC12B (Table 2). CLEC12B is unusual as it is the only known receptor within the DECTIN-1 cluster, which acts as an inhibitory receptor via recruitment of Src homology phosphatase (SHP)-1 and SHP-2 [20]. We have demonstrated that human CLEC12B has several splice variants, and many of them are likely to render the corresponding protein nonfunctional.…”
Section: Clec12bmentioning
confidence: 99%